APPLICATION OF SPECTRAL DECOMPOSITION IN PALEOGEOGRAPHY INTERPRETATION OF LACUSTRINERIFT SYSTEM OF NORTH AMAN SUB-BASIN, CENTRAL SUMATRA BASIN - Suhirmanto, Agus
Spectral decomposition has been applied in seismic data processing and interpretation for years. In reservoir characterization purposes, spectral decomposition method mostly used to produce an accurate image that can reduces the sub-surface geological interpretation uncertainties and ambiguities such as fault system and also the geometry of depositional facies distribution. Principally, spectral decomposition offers an affective approach in phase independent amplitude spectrum usage and designed to know better about thin bed respond in 3D seismic data. The application of spectral decomposition method in North Aman Paleogene Subbasin, Central Sumatra Basin, which interpreted as rift basin, produces a significant improvement in imaging the sub-surface geological condition in each rift development system tract e.g. fault system, geometry of depositional facies such as meandering and braided fluvial (channel), alluvial fans, and lacustrine delta. Special for rift climax sequence that associated as depositional sequence of Brownshale and Upper Red Beds Formation (Sand 4930’), spectral decomposition method is proven can improve significantly sub-surface geological feature imaging. Thus, it can be used to reduce uncertainties in geological interpretation. Normal fault system as control of this rift development can be identified in NE-SW trend. While depositional facies such as braided fluvial system can be identified in relatively N-SE direction and alluvial fan is identified being developed from border fault at NW direction towards rift depocenter. Further analysis of spectral decomposition can be used to determine quantitatively this depositional facies thickness.